ANALISIS PENGARUH MIGRASI MASUK TERHADAP PERMINTAAN RUMAH SEDERHANA DI KOTA PEKANBARU - Wahyu Hamidi '; Muhammad Hasbi ' (Jurnal Ekonomi, 2014)
The research was conducted in the city of Pekanbaru in March-August 2013. The purpose of this study was to analyze the effect of migration on housing demand in the city of Pekanbaru is simple. The data used in this study is secondary data time series from 2001 until 2010. The method of analysis used in this study was descriptive quantitative method with a simple linear regression analysis. With SPSS version 17. From the results of the tests, t tests showed that the migration variable positive effect on demand for a modest home in Pekanbaru. Based on the calculation of the correlation coefficient (R) obtained R value of 0.756 means that the closeness of the linear relationship between the level of in-migration to a request for simple house is 75.6%, indicating that the relationship between the two variables is very close. Furthermore, based on the calculation of the coefficient of multiple determination (R2) obtained R2 value of 0.572 indicating that the rate of in-migration affects demand a modest home that is equal to 57.2%, while 42.8% are influenced by other factors not addressed in this study.Kata Kunci : Housing Demand Simple, Migasi Login